Service excellence : creating customer experiences that build relationships - Bolton, Ruth N. (Marketing strategy collection., 2016)
Service has a unique ability to create experiences that build profitable relationships with customers. Based on a service-centered perspective, this book analyzes the challenges of creating excellent customer experiences, including the management of technology and new media. It describes how customers coproduce and cocreate their experiences, and how these activities influence business revenues and costs. Customer Experience refers to the sensory, cognitive, emotional, social, and behavioral dimensions of all activities that connect the customer and the organization over time across touchpoints and channels. It encompasses all activities involving the customer where the organization is the focal object, including prepurchase activities (such as exposure to a website ad), and purchase, consumption, and engagement behaviors (blogging, sharing photos). The book takes a deep dive into the psychology of customers, revealing the conceptual building blocks of customer experiences and how they build relationships over time. These ideas provide a business perspective on how customer-focused service strategies generate cash flows, including the role of pricing.